Nannofossil absolute abundances of sediment core GeoB1117-2 - Karl-Heinz Baumann; Hanno Kinkel (PANGAEA, 2025)
The present study was initiated to ascertain the significance of coccolithophores as a proxy for paleoceanographic and paleoproductivity studies in the equatorial Atlantic. Data from a range of different samples, from the plankton, surface sediments as well as sediment cores are shown and compared with each other. During the past 140,000 years the surface water circulation of the equatorial Atlantic has changed drastically, as can be seen from changes in the coccolithophore species composition, absolute coccolith numbers. Significant increases in coccolith numbers and accumulation rates is observed in the southern equatorial Atlantic during the last glacial interval (oxygen isotope stages 2–4), which we attribute to enhanced upwelling intensities and advection of cool nutrient-rich waters at this site. In the western equatorial Atlantic we observe an opposite trend with decreasing numbers of coccoliths during glacial periods, which probably is caused by a deepening of the thermocline.